PENGARUH BREED TERHADAP MOTILITAS SPERMA SAPI LOKAL INDONESIA DAN Bos taurus DI BALAI INSEMINASI BUATAN (Effect breeds on sperm motility of indonesian local bulls and bos taurus at Artificial Insemination Center) - M. Hasan; Annisa Rahmi; R. Handarini; T. Maulana; S. Said; E. M. Kaiin; A. Baharun (JURNAL NUKLEUS PETERNAKAN, 2023)
The attempt to achieved the goal could be through using artificial insemination (AI) by frozen semen. This study aims to evaluate the effect of the breed on sperm motility using Madura, Bali bulls and Bos taurus frozen semen. The experiment used local bull frozen semen (Madura and Bali bull breeds) and Bos taurus bull (Simmental and Limousin breeds) produced by Singosari’s artificial insemination center. Sperm motility evaluation was conducted using computer-assisted sperm analysis (CASA, Spermvision, Minitube®, Germany). The analyzing data uses a generalized linear model, one-way ANOVA using the SPSS 26 software. Duncan’s multiple range test (DMRT) was used to determine any significant differences. The result shows for total motility (TM) and progressive motility (PM) are 63.89±1.72% and 54.38±4.39% (Madura bull), 51.48±3.30% and 42.47±5.48% (Bali bull), 58.21±1.13% and 44.38±3.15% (Simmental bull), also 58.12±1.64% and 51.49±3.03% (Limousin bull). There is no differential sperm motility (P>0.005) in both parameters for all breeds. All frozen semen used in this study qualifies with Indonesian National Standards and is approved for use in the artificial insemination program.